2020
DOI: 10.1055/s-0040-1708799
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes with Longer Second Stage of Labor: A Risk Analysis Comparing Expectant Management to Operative Intervention

Abstract: Objective The aim of this study is to assess the impact of a prolonged second stage of labor on maternal and neonatal outcomes by comparing women who had expectant management versus operative intervention beyond specified timeframes in the second stage of labor. Study Design Retrospective cohort including live singletons at ≥36 weeks who reached the second stage of labor. Expectant management (second stage >3, 2, 2, and 1 hour in nulliparas with an epidural, nulliparas without an epidural, multipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Thuillier C and Zipori Y reported the new consensus recommendations was associated with the reduction of the rate of primary cesarean delivery [6,19]. Ausbeck EB's research showed prolonged second stage was associated with adverse maternal outcomes significantly, but not with adverse neonatal outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thuillier C and Zipori Y reported the new consensus recommendations was associated with the reduction of the rate of primary cesarean delivery [6,19]. Ausbeck EB's research showed prolonged second stage was associated with adverse maternal outcomes significantly, but not with adverse neonatal outcomes [20].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the duration of the second stage of labor on perinatal outcomes has been well studied. E. B. Ausbeck’s retrospective cohort study showed that prolonged second stage was associated with adverse maternal outcomes such as PPH, chorioamnionitis, operative complications, postpartum infections, and ICU admission, but not with adverse neonatal outcomes [ 18 ]. Several studies also reported that multiparous women were at increased risk for operative deliveries, peripartum morbidity, and adverse neonatal outcomes with the second stage of 3 h or greater [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…By grouping the 2,140 cases with a group spacing of 60 minutes, we revealed that after 1 hour of second stage, each 60-minute increase in the length of labor did not significantly change neonatal UABGA pH, BE, or lactate, suggesting that the current limit of 4 hours (nulliparous) or 3 hours (multiparous) for the length of the second stage of labor does not significantly increase the risk of adverse outcomes such as metabolic acidosis in neonates. Previous studies showed that the effect of prolonged second stage of labor (>3 hours in nulliparous/2 hours in multiparous women) on neonatal outcome was inconclusive (12,13). However, they failed to discuss cases prolonged over 4 hours in the second stage of labor, as they were limited by the old management model of labor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the effect of prolonged second stage of labor (>3 hours in nulliparous/2 hours in multiparous women) on neonatal outcome was inconclusive ( 12 , 13 ). However, they failed to discuss cases prolonged over 4 hours in the second stage of labor, as they were limited by the old management model of labor stage.…”
Section: Discussionmentioning
confidence: 99%